Comparison of Construction Policies of Shandong and Guangdong Maritime Powerhouses: Based on text analysis - Yongping LI; Aidong ZHANG (Haiyang Kaifa yu guanli, 2024)
The sea is a strategic place to achieve high-quality development in the new stage of development, and its role in the development of the national economy is becoming increasingly prominent. This paper uses text analysis to analyze the policy documents on the construction of a strong maritime province issued by the government departments of Shandong and Guangdong from 2010 to 2020, and makes statistical analysis and comparison from four dimensions: promulgation entity, policy type, language type, keywords and semantic network. The results show that from the perspective of promulgation subjects, Shandong Province emphasizes interdepartmental cooperation and coordination, and Guangdong emphasizes the authority of policy implementation. From the perspective of policy type, Shandong places more emphasis on the standardized supervision of offshore islands, industrial regulation and the use of financial funds, while Guangdong places more emphasis on the division of functional areas and marine ecological protection. From the perspective of type of language, the structure of the two provinces is similar, but Shandong is more inclined to management methods; From the perspective of keyword frequency and semantic network analysis, Shandong focuses on promoting marine fishery construction and resource development, while Guangdong pays more attention to ecological protection and resource utilization. Finally, four policy enlightenments for the construction of Shandong Ocean Power Province are obtained.